PENGARUH LOKASI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Kasus Pada Konsumen KFC Dermaga Point Palembang) - Puspitasari Puspitasari; Dian Eka; Welly Nailis (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2018)
This study was conducted to determine and analyze the effect of Location (X1) and Brand Image (X2) on The Purchase Decision (Y) on the consumer KFC Pier Point Palembang. This study uses primary data obtained through questionnaires, samples taken by 100 respondents using method purposive sampling. The analysis technique used is multiple regression analysis, F test and T test results of research on the F test showed a significant value of 0.000, which means independent variables consisting of Location (X1) and Brand Image(X2) together (simultaneously) the positive effect and significant impact on Purchase Decision (Y) in purchase and consume products in KFC Pier Point Palembang. The study also showed partial that variable Location (X1) and Brand Image (X2) has positive and significant influence on the Purchase Decision (Y) in purchase and consume products in KFC Pier Point Palembang. Keywords : location and brand image, purchase decision